Regenerative morphological traits in a woody species community in Tumbesian tropical dry forest [Rasgos morfológicos regenerativos en una comunidad de especies leñosas en un bosque seco tropical tumbesino] - Romero Saritama, J. (2016)
The study of functional morphological traits enables us to know fundamental aspects of the dynamics of plant communities in local and global habitats. Regenerative morphological traits play an important role in defining plant history and ecological behavior. Seed and fruit characteristics determine to a large extent the patterns for dispersal, germination, establishment and seedling recruitment a given species exhibits on its natural habitat. Despite their prominent role, seed and fruit traits have been poorly studied at the community level of woody plant species in neo-tropical dry forests. In the present study we aimed at i) evaluate the functional role of morphological traits of seeds, fruits and embryo in woody plant species; ii) determine which are the morphological patterns present in seeds collected from the community of woody species that occur in neo-tropical dry forests; and iii) compare woody plant species seed mass values comparatively between neo-tropical dry and tropical forests. To do so, mature seeds were collected from 79 plant species that occur in the Tumbesian forest of Southwest Ecuador. The studied species included the 42 and 37 most representative tree and shrubbery species of the Tumbesian forest respectively. A total of 18 morphological traits (seven quantitative and 11 qualitative) were measured and evaluated in the seeds, fruits and embryos of the selected species, and we compared the seeds mass with other forest types. Our results showed a huge heterogeneity among traits values in the studied species. Seed mass, volume and number were the traits that vary the most at the community level, i.e. seed length ranged from 1.3 to 39 mm, and seed width from 0.6 to 25 mm. Only six embryo types were found among the 79 plant species. In 40 % of the cases, fully developed inverted embryos with large and thick cotyledons to store considerable amount of nutrients were recorded. We concluded that highly variable and functionally complementary morphological traits occur among the studied woody plants of the Tumbesian dry forest. The latter favors a plethora of behavioral mechanisms to coexist among woody species of the dry forest in response to the environmental stress that is typical of arid areas. © 2016, Universidad de Costa Rica. All rights reserved.